Review: Cope, Emily M. Evangelical Writing in a Secular Imaginary: The Academic Writing of Christian Undergraduates at a Public University. - Kelly M Sauskojus (Journal of the Assembly for Expanded Perspectives on Learning, 2025)
Emily Murphy Cope’s Evangelical Writing in a Secular Imaginary: The Academic Writing of Christian Undergraduates at a Public University (2024) empirically considers how evangelical students negotiate their identities in their academic writing.